2021
DOI: 10.1126/sciadv.abe2597
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeler ISWI acts during Drosophila development to regulate adult sleep

Abstract: Sleep disruptions are among the most commonly reported symptoms across neurodevelopmental disorders (NDDs), but mechanisms linking brain development to normal sleep are largely unknown. From a Drosophila screen of human NDD-associated risk genes, we identified the chromatin remodeler Imitation SWItch/SNF (ISWI) to be required for adult fly sleep. Loss of ISWI also results in disrupted circadian rhythms, memory, and social behavior, but ISWI acts in different cells and during distinct developmental times to aff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…Our studies and recent findings ( Gong et al, 2021 ) suggest that proper regulation of neurogenesis is essential for normal sleep and that altered neurogenesis in discrete circuits can cause lifelong sleep dysfunction. Intriguing but fragmentary evidence suggests that other genes whose mutation impacts sleep might similarly alter neurogenesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our studies and recent findings ( Gong et al, 2021 ) suggest that proper regulation of neurogenesis is essential for normal sleep and that altered neurogenesis in discrete circuits can cause lifelong sleep dysfunction. Intriguing but fragmentary evidence suggests that other genes whose mutation impacts sleep might similarly alter neurogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…Here, we have used temporally restricted genetic manipulations to show that inc acts during neuronal development to ultimately impact sleep in adulthood. While many genes are known to act in adults to impact sleep, developmental mechanisms underlying sleep regulation have only recently gained attention ( Chakravarti Dilley et al, 2020 ; Gong et al, 2021 ; Iwasaki et al, 2021 ; Xie et al, 2019 ). Our results underscore the importance of unbiased temporal genetic manipulations to define critical periods through which genes impact sleep, and suggest that genes may influence sleep through unappreciated developmental mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…4, C to E ). Consistent with these findings, Gong et al ( 47 ) reported that Iswi knockdown in flies results in mushroom body morphologic abnormalities, as well as disrupted sleep, circadian rhythmicity, memory, and social behaviors, suggesting that Iswi is required during development for numerous adult behaviors.…”
Section: Resultsmentioning
confidence: 68%
“…Apart from its previously reported function in cell proliferation/stem cell self-renewal ( 59 ) and hence smaller head/microcephaly, we identified its requirement in postmitotic neurons. Specifically, we found that Iswi LoF leads to defects in sensory neuron dendrite tiling and mushroom body development, highlighting its underappreciated role in neural circuit assembly ( 47 ). This likely contributes to the behavioral deficits such as impaired locomotion in the Iswi knockdown flies and intellectual disability, hypotonia, and speech delay in patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation